Courtesy and idleness: Gender differences in team work and team competition - Radosveta Ivanova-Stenzel; Dorothea Kübler (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
Does gender play a role in the context of team work? Our results based on a real-effort experiment suggest that performance depends on the composition of the team. We find that female and male performance differ most in mixed teams with revenue sharing between the team members, as men put in significantly more effort than women. The data also indicate that women perform best when competing in pure female teams against male teams whereas men perform best when women are present or in a competitive environment.
Keywords: C72; C73; C91; D82; 330; team incentives; gender; tournaments